Potential antibacterial activity of Avicennia marina extract against pathogenic bacteria - Rosa, Kamelia; Hidayah, Oktavia Nur; Sofyanti, Dhiya’ul Auliyah; Diswantoro, Reza Dwi; Zulkiflih, Mochammad Ivan; Fuadi, Mohamad Tanwirul (Journal of Marine Resources and Coastal Management, 2024)
Avicennia marina, a mangrove plant, is renowned for its medicinal properties, particularly its antibacterial potential. Phytochemical analysis of the plant revealed the presence of bioactive compounds such as alkaloids, terpenoids, and flavonoids, which are known to contribute to its antibacterial effects. This study investigates the antibacterial activity of Avicennia marina leaf extract against Staphylococcus aureus and Escherichia coli. The research employed three main methods: preparation of Nutrient Agar (NA) and Nutrient Broth (NB) as growth media, extraction of bioactive compounds from Avicennia marina leaves, and antibacterial testing at concentrations of 0.1 and 0.2 grams on each medium. The results showed that the leaf extract effectively inhibited the growth of Staphylococcus aureus when using NB, with inhibition zones measuring 6.47 mm and 12.26 mm, indicating a bacteriostatic effect. In contrast, no inhibition zones were observed when using NA, suggesting that the growth medium plays a critical role in determining antibacterial effectiveness. These findings underscore the significant potential of Avicennia marina leaf extract as a natural antibacterial agent, particularly against Staphylococcus aureus, and highlight the importance of selecting suitable media and testing methods. This study paves the way for future research into the development of Avicennia marina-based nutraceuticals and pharmaceuticals, with potential applications in healthcare and bacterial infection management.